HBR guide to performance management. (Boston Massachusetts : Harvard Business Review Press, 2017)
Are your employees meeting their goals? Is their work improving over time? Understanding where your employees are succeeding--and falling short--is a pivotal part of ensuring you have the right talent to meet organizational objectives. In order to work with your people and effectively monitor their progress, you need a system in place. The HBR Guide to Performance Management provides a new multi-step, cyclical process to help you keep track of your employees' work, identify where they need to improve, and ensure they're growing with the organization. You'll learn to: Set clear employee goals that align with company objectives Monitor progress and check in regularly Close performance gaps Understand when to use performance analytics Create opportunities for growth, tailored to the individual Overcome and avoid burnout on your team--
Introduction: Rethinking traditional performance management -- Section 1. Goal setting: The characteristics of effective goals: Make them clear and specific, achievable but challenging -- Define employee goals - and decide how they're measured, fit the needs of the individual and the organization -- Collaborate with your employee to create a plan for moving forward : steps to accomplishing objectives and adjusting as necessary -- Section 2. Ongoing performance management : Assessing performance isn't a one-time event : take note of good and bad work, and assess root cause -- Develop a habit of providing feedback : discuss your observations with your employee -- Coach your employee to close performance gaps : work together to create a plan for improvement -- How to keep your employees motivated : recognize good work and encourage progress -- Section 3. Developing employees : Understand your employee's wants and needs : know what your direct report aspires to -- Expand your employee's skillsets : basic tactics to learn new areas of expertise -- Craft a development plan : define a specific path for future growth -- How to develop someone who's struggling : good performers aren't the only ones who need to grow -- Section 4. Formal performance reviews : The case against (and for) annual appraisals : how companies are changing the way they look at reviews -- Assess performance, but reconsider ratings : take an individualized approach -- How to conduct the review conversation : tips and tricks for a productive discussion -- Define new goals for the new year : adjust objectives for continued growth -- Section 5. Tough topics: Responding to the steady worker : what to do with your stalwarts -- Preventing burnout on your team : make sure your people aren't running out of steam -- Managing performance of remote employees : from giving feedback to annual assessments.
Keywords: Employees -- Rating of; Performance -- Management